New York City’s response to COVID-19 in the context of the smart city concept - Kozak, Alicja (Odpowiedź Nowego Jorku na COVID-19 w kontekście koncepcji inteligentnego miasta, 2024)
Aim: This study aims to critically assess how New York City’s response to the COVID-19 pandemic aligns with the principles of the smart city concept. Expanding upon an earlier study focused on the initial, ad hoc urban responses, this research examines the entire duration of the pandemic, highlighting strategic shifts and long-term adaptations in crisis management and urban resilience. Methodology: The study employs a case study approach, analysing policy documents, statistical data, and secondary sources to assess New York City’s transition from immediate crisis response to structured recovery efforts. A qualitative assessment of governance strategies, social equity measures, and sus-tainability policies forms the basis of the evaluation. Results: The study reveals that while New York City made strides in job recovery and economic revitalization, its response to the COVID-19 pandemic exposed persistent disparities in digital access, environmental justice, and social equity. The city implemented smart city-aligned initiatives, such as digital transformation efforts and sustainability programs, but challenges in governance, public trust, and equitable resource distribution hindered comprehensive resilience. The uneven recovery process highlighted gaps in long-term crisis management, emphasizing the need for a more inclusive and adaptive approach to urban resilience. Implications and recommendations: The study underscores the necessity for a more integrated and inclusive approach to urban crisis management. It highlights the importance of addressing systemic inequalities and ensuring equitable access to technology and resources to fully realize the smart city vision. Originality/value: This research contributes to the discourse on smart city resilience by offering a longitudinal perspective on New York City’s pandemic response. It provides valuable insights into the complexities of urban governance in times of crisis and the role of smart city strategies in fostering sustainable recovery.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 49-61
Keywords: Dolny Śląsk